Chronic hepatitis associated with antiribosomal‐P autoantibodies in a 14‐year‐old girl. Issue 10 (5th September 2019) - Mejean, Coline; Bertin, Daniel; Guetta, Kim; Desaldeleer, Cécile; Butori, Mathilde; Roquelaure, Bertrand; Fabre, Alexandre
Abstract: We reported the first pediatric case of auto‐immune hepatitis with positive anti‐P antibodies. On the basis of our findings, adding auto anti‐P screening in pediatric seronegative HAI may be recommended. Abstract : We reported the first pediatric case of auto‐immune hepatitis with positive anti‐P antibodies. On the basis of our findings, adding auto anti‐P screening in pediatric seronegative HAI may be recommended.